Crime classification manual: a standard system for investigating and classifying violent crimes - Douglas, John E. (Jossey-Bass, 2006)
Modus operandi and the signature aspects of violent crime / John E. Douglas and Lauren K. Douglas -- The detection of staging, undoing, and personation at the crime scene / John E. Douglas and Lauren K. Douglas -- Prescriptive interviewing : interfacing the interview and interrogation with crime classification / Gregory M. Cooper -- Classifying crimes by severity : from aggravators to depravity / Michael Welner -- VICAP : The Violent Criminal Apprehension Program Unit / Eric W. Witzig -- Homicide -- Arson, bombing -- Rape and sexual assault -- Nonlethal crimes -- Computer crimes / Allen G. Burgess -- Cybercrimes / John E. Douglas and Lauren K. Douglas -- Classifying internet child sex offenders / Eileen M. Alexy, Ann W. Burgess, and Timothy Baker -- Mass, spree, and serial homicide / Ann W. Burgess -- Homicidal poisoning / Arthur E. Westveer, John P. Jarvis, and Carl J. Jensen III -- The use of biological agents as weapons / Anne M. Berger -- Wrongful convictions : causes, solutions, and case studies / Peter Shellem -- Criminal confessions : overcoming the challenges / Michael P. Napier and Susan H. Adams